Porcelaneous larger foraminiferal responses to Oligocene–Miocene global changes - Bassi, Davide; Braga, Juan Carlos; Pignatti, Johannes; Fujita, Kazuhiko; Nebelsick, James H.; Renema, Willem; Iryu, Yasufumi (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)
Sea surface temperatures (SST) have been identified as a main controlling factor on larger benthic foraminifera (LBF) living in tropical to sub-tropical shallow-water carbonate and mixed siliciclastic‐carbonate platforms. Changes in SST, along with those in ocean acidification and nutrient content recorded in the global oceans throughout their history will not only continue but also be amplified in the future at an unprecedented rate of change possibly reaching levels found in the geological record. This study focuses on the Oligocene (mean SST 8 °C higher than present) and the Miocene (SST 5–8 °C higher than present) epochs which were characterized by a higher richness in porcelaneous LBF (pLBF) than today. A systematic re-assessment and comprehensive literature survey of stratigraphic ranges and palaeogeographic distribution in the Western Tethyan (Mediterranean) and Indo-Pacific regions are used to evaluate the impact of changes in SST, seawater pCO2 and pH on the biodiversity of the Oligocene–Miocene pLBF Alveolinella, Austrotrillina, Borelis, Bullalveolina, Flosculinella, and Praebullalveolina. Two peaks in species richness were identified during the Aquitanian and Langhian–Serravallian. These peaks occurred when SST was ∼29 °C, with pCO2 of ∼400 ppm and pH > 7.8. These values are comparable to those of today. The minima in species richness recorded in the Rupelian–early Chattian, in the Burdigalian and from the Tortonian onward can be correlated to the detrimental effects of both minimum (< 26 °C) and maximum (> 31 °C) SST thresholds. High pCO2 (> 600 ppm) values, which are limited to the Rupelian–early Chattian, are also detrimental to species richness. Seawater pH higher than 7.7 did not negatively affect species richness. These historical trends have serious implications for the future diversity of pLBFs with the increasing likely scenario of rising SST and pCO2 and lowering of pH values in the near future. These developments can potentially lead to diversity decrease and even extinction of ...